GENETIC DIVERSITY OF PHYTOPATHOGENIC BACTERIA, Ralstonia solanacearum (Smith) Yabuuchi et al. INFECTING HORTICULTURAL PLANTS IN JAVA ISLAND, INDONESIA, AND SCREENING OF ANTAGONISTIC SOIL BACTERIA AGAINST R. solanacearum - Merry Hemelda, Niarsi
Ralstonia solanacearum is a phytopathogenic bacteria causing bacterial wilt disease in many important crops in Indonesia. However, less study has been done on its genetic diversity in Indonesia. The aims of this study were to determine the genetic diversity of R. solanacearum in Java Island and do screening of antagonistic soil bacteria against R. solanacearum. Bacteria inside the stems of infected plants were isolated from three provinces (West Java, Central Java, and East Java) in Java Island. The obtained bacteria were then tested whether they were virulent to plant using tobacco leaf injection hypersensitive response test. The virulent isolates were identified using PCR technique with primers specific to R. solanacearum species complex. Phylotype-specific multiplex PCR (Pmx-PCR) technique was performed on the positive isolates of R. solanacearum species complex to distinguish R. solanacearum from the other two closely-related bacteria (R. syzygii and BDB) which belonged to R. solanacearum species complex, and identify which phylotype a strain belonged to. Genetic diversity of R. solanacearum isolates was determined using two methods: BOX-PCR genomic fingerprinting and phylogenetic analysis of mutS gene sequences. BOX-PCR was carried out to determine the genetic diversity of R. solanacearum at strain level, and choose the representative isolates for mutS gene phylogenetic analysis. The phylogenetic analysis of the mutS gene was performed to confirm the phylotype identification using Pmx-PCR, and determining the relationship of R. solanacearum isolates with the reference strains. Antagonistic soil bacteria against R. solanacearum was obtained by (1) identifying 25 soil bacterial isolates from the Laboratory of Plant Pathology PT. East West Seed Indonesia collection using PCR technique and 16S rRNA gene sequencing, then (2) testing their antagonistic activities against R. solanacearum using dual-culture technique. A total of 28 R. solanacearum isolates was isolated from five crop species (pepper, eggplant, tomato, common bean, and watermelon). Based on hypersensitive response test, all isolates were virulent. Phylotype identification using Pmx-PCR showed that 27 isolates belonged to phylotype I (Asiaticum), while one isolate belonged to phylotype II (Americanum). BOX-PCR analysis revealed eight patterns of DNA bands: 7 patterns belonged to phylotype I, while one pattern belonged to phylotype II. Dendrogram analysis of BOX-PCR showed that isolates from West Java and Central Java were clustered according to their original provinces, except isolates from East Java which were spread into cluster 6, 7, and 8. Based on phylogenetic analysis of the mutS gene of 14 representative isolates, isolates identified as phylotype I using Pmx-PCR were grouped in the “Phylotype iv I” cluster, while IDGR3114 isolate identified as phylotype II using Pmx-PCR was in the “Phylotype IIB” of the phylogenetic tree. It was confirmed that Pmx-PCR result was similar to phylogenetic analysis of mutS gene. Identification of the 25 soil bacterial isolates using 16S rRNA gene sequences showed that those isolates belonged to six species of three families: Xanthomonadaceae, Pseudomonadaceae, and Brucellaceae. Based on antagonistic test of the 25 soil bacterial isolates, two isolates were able to inhibit the growth of R. solanacearum: Pseudomonas taiwanensis and P. plecoglossicida. In conclusion, most of R. solanacearum in Java Island was R. solanacearum phylotype I, but R. solanacearum phylotype IIB was also reported. The Pmx-PCR technique was able to be applied for phylotype identification of R. solanacearum strains from Indonesia. The BOX-PCR technique showed more discriminatory power at subphylotype level than phylogenetic analysis of mutS gene. In addition, Pseudomonas taiwanensis and P. plecoglossicida were potential as biocontrol agents for bacterial wilt disease because of their antagonistic activities against R. solanacearum.